THE RELATIONSHIP BETWEEN FINANCIAL LITERACY LEVELS AND INVESTMENT BEHAVIOR: UNDERSTANDING THROUGH CAUSAL LOOP DIAGRAM - Jones Parlindungan Nadapdap; Rissa Ayustia; Jorge Ribeiro Freitas; Aloysius Hari Kristianto; Listra Frigia Missianes Horhoruw (SEAN Institute, 2023)
This research aims to provide an overview of the factors that influence a person's or individuals' investment behavior. The aspects modeled in this study are internal and external. The result is a picture of the relationship between financial literacy and investment intention. Financial literacy is represented by knowledge, skills, and competencies, while investment interest is represented by attitudes, subjective norms, and perceived behavioral control. The investment interest relation employs the theory of planned behavior (TPB), which proposes that a person's or individual's investment behavior is influenced by attitudes, subjective norms, and perceived behavioral control. This study's methodology is system dynamics, which is based on the concept of feedback from control theory and causal loops. In this study, a causal loop diagram approach was used, namely a feedback loop system in a diagram, and this is a feedback structure communication tool that represents the system's main feedback loop that produces the system's dynamic reference behavior.